Application of simple seismic models for interpretation of small reef objects under conditions of low resolution seismic data and incomplete borehole information - BARMUTA, Jan; PIETSCH, Kaja (Geology, Geophysics and Environment, 2011)
Tracing facies and saturation with hydrocarbon along sedimentary beds is one of Seismic's most important objectives. The application of simple seismic modeling for the interpretation of low resolution seismic data is presented. This method confirmed the possibility to trace changes in Main Dolomite (Ca2) development and to detect, comparatively small to the seismic resolution, hydrocarbon traps.